Cerebrospinal fluid tau, Aβ, and sTREM2 in Former National Football League Players: Modeling the relationship between repetitive head impacts, microglial activation, and neurodegeneration. Issue 9 (23rd July 2018) - Alosco, Michael L.; Tripodis, Yorghos; Fritts, Nathan G.; Heslegrave, Amanda; Baugh, Christine M.; Conneely, Shannon; Mariani, Megan; Martin, Brett M.; Frank, Samuel; Mez, Jesse; Stein, Thor D.; Cantu, Robert C.; et al.
Abstract: Introduction: Cerebrospinal fluid (CSF) protein analysis may facilitate detection and elucidate mechanisms of neurological consequences from repetitive head impacts (RHI), such as chronic traumatic encephalopathy. We examined CSF concentrations of total tau (t‐tau), phosphorylated tau, and amyloid β1‐42 and their association with RHI in former National Football League (NFL) players. The role of microglial activation (using sTREM2) was examined as a pathogenic mechanism of chronic traumatic encephalopathy. Methods: Sixty‐eight former NFL players and 21 controls underwent lumbar puncture to quantify t‐tau, p‐tau181, amyloid β1‐42, and sTREM2 in the CSF using immunoassays. The cumulative head impact index estimated RHI. Results: No between‐group differences for CSF analytes emerged. In the former NFL players, the cumulative head impact index predicted higher t‐tau concentrations ( P = .041), and higher sTREM2 levels were associated with higher t‐tau concentrations ( P = .009). Discussion: In this sample of former NFL players, greater RHI and increased microglial activation were associated with higher CSF t‐tau concentrations.